Optimalisasi Peran Forum Anak Desa dalam Mensosialisasikan Kebijakan Kota Layak Anak di Desa Lembengan Kecamatan Ledokombo Kabupaten Jember - Arifin, Sahrul; Khotimah, Khusnul; Baladudin Dayar, Mohammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2024)
Abstract Optimizing the Role of the Village Children's Forum in Socializing the Child-Friendly City Policy in Lembengan Village, With the availability of this organization and the government's commitment to the constitution and local regulations, children will be able to take full advantage of this opportunity by starting to contribute by creating positive activities that bring change, by inviting others around them, both in the family, school and community, as well as reporting inappropriate incidents related to not respecting children's rights, remembering that children are the future of the nation and the successor of the nation's ideals. The theory used in this study, using Horton and Hunt's theory, explains that role is the behavior that is expected of a person who has a status. Everyone may have a number of statuses and are expected to fill in according to those statuses. In a sense, status and role are two aspects of the same phenomenon. Status is a set of rights and obligations, a role is the actor of a set of rights. The socialization of the Child-Friendly City Policy in Lembengan Village focuses on three contents: 1), prevention of early pregnancy, 2), prevention of illegal pregnancy, 3), sexual violence and gende. All efforts that have been made by the Lembengan Village Children's Forum in Optimizing the Role of the Village Children's Forum in Socializing the Child-Friendly City Policy in Lembengan Village such as socialization through distributing berosur in the village carnival event, conducting socialization to elementary schools, socialization of children's play rights in the Tanuker Hall Building and also the Children's Forum in Lembengan Village using online media for socialization of online-based gender violence. carried out by the Children's Forum in Lembengan Village in Optimizing the Child-Friendly City Policy is still not optimal because there is still a lack of understanding of the Lembengan Village Residents to implement the Children's Laya City Policy in Lemebengan Village, Jember Regency